2023
DOI: 10.1186/s12967-023-03902-4
|View full text |Cite
|
Sign up to set email alerts
|

Lipolysis and gestational diabetes mellitus onset: a case-cohort genome-wide association study in Chinese

Abstract: Background Genetic knowledge of gestational diabetes mellitus (GDM) in Chinese women is quite limited. This study aimed to identify the risk factors and mechanism of GDM at the genetic level in a Chinese population. Methods We conducted a genome-wide association study (GWAS) based on single nucleotide polymorphism (SNP) array genotyping (ASA-CHIA Bead chip, Illumina) and a case-cohort study design. Variants including SNPs, copy number variants (CNV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 73 publications
0
2
0
2
Order By: Relevance
“…In addition to its preference for short carbon chain substrates [ 30 ], Shirli et al reported that the LIPN gene encoding epidermal lipase N has been linked to congenital ichthyosis with a late-onset form associated with autosomal-recessive inheritance [ 31 ]. In another paper, gestational diabetes mellitus was associated with lipolysis-related genes such as LIPN [ 32 ]. However, there are few studies on LIPN in autoimmune diseases, especially SSc with ILD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its preference for short carbon chain substrates [ 30 ], Shirli et al reported that the LIPN gene encoding epidermal lipase N has been linked to congenital ichthyosis with a late-onset form associated with autosomal-recessive inheritance [ 31 ]. In another paper, gestational diabetes mellitus was associated with lipolysis-related genes such as LIPN [ 32 ]. However, there are few studies on LIPN in autoimmune diseases, especially SSc with ILD.…”
Section: Discussionmentioning
confidence: 99%
“…При использовании полногеномного поиска ассоциаций (GWAS) варианты генов проверяются на наличие какой-либо связи с признаком или с заболеванием по всему геному непредвзятым образом, без гипотез. На сегодняшний день выполнено четыре GWAS для ГСД [29][30][31][32][33].…”
Section: том 3 № 6 2023unclassified
“…Исследования показывают, что мелатонин стимулирует секрецию глюкагона и инсулина в α-и β-клетках поджелудочной железы [34]. Метаболические и другие эффекты мелатонина опосредованы связыванием с трансмембранными рецепторами, связанными с G-белком, MT 1 и МТ 2 , последний из которых кодируется MTNR1B [33]. Варианты гена MTNR1B связаны не только с СД2, но и с изменениями важных маркеров метаболизма, включая глюкозу натощак, гликированный гемоглобин, раннюю секрецию инсулина в ответ на введение глюкозы, и скорость снижения секреции инсулина [34].…”
Section: том 3 № 6 2023unclassified
“…The first four loci are also associated with T2DM, while, as described in more detail below, HKDC1 was previously associated with maternal glycemia during pregnancy [ 49 ]. A final, recent GWAS performed in a Chinese population that included 193 women with GDM and 819 controls failed to identify any SNPs significantly associated with GDM [ 50 ]. Fourteen regions that contained copy number variants (CNVs) were significantly associated with GDM, but none of these were in genetic regions previously associated with GDM.…”
Section: Genetics Of Gdmmentioning
confidence: 99%